Multilateral Loans and Interest Rates: Further Evidence on the Seniority Conundrum - Sven Steinkamp; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2016)
During Europe's sovereign-debt crisis, interest rate spreads have been highly correlated with the share of multilateral loans that were considered senior to private markets. As both variables are potentially endogenous, we follow two different approaches to analyze the direction of causality. First, we use a set of IV regressions where the differences between sovereign ratings serve as instruments. Second, we analyze a new panel-survey dataset on seniority and interest rate expectations. In both approaches, we find evidence for the seniority conundrum – i.e., a positive impact of multilateral loans on interest rate spreads.
Keywords: F34; G12; H81; 330; government bond spreads; creditor seniority; recovery rate; interest rate; sovereign debt